Synthesis and characterization of two different azarubrenes - Xie, Gaozhan; Hahn, Sebastian; Rominger, Frank; Freudenberg, Jan; Bunz, Uwe H. F. (Chemical communications, 2018)
The synthesis, properties and solid state X-ray single crystal structures of two new rubrene-derivatives, viz diazarubrene (4,4′-(6,12-diphenyltetracene-5,11-diyl)dipyridine) and tetraazarubrene (5,6,11,12-tetra(pyridin-4-yl)tetracene), are reported. Both the azarubrenes are more oxidatively stable than rubrene itself and show very similar optical properties but differ in their crystal packing from that of rubrene.
Gesehen am 09.04.2020